Guarding Integrity in Islamic Banking: The Role of Fiqh Muamalah, Religiosity, and Fraud Intention in Shaping Ethical Behavior - Mohamad Heykal; Etty Murwaningsari; Sekar Mayangsari (Shirkah: Journal of Economics and Business, 2025)
Fraud remains a persistent challenge in the banking sector, including Islamic financial institutions normatively grounded in Sharia principles. This study examines how fiqh muamalah and religiosity influence fraud intention and fraudulent behavior among internal accountants in Islamic banks, with fraud intention positioned as a mediating mechanism. Using a quantitative explanatory survey design, data were collected from 260 internal accountants employed in Islamic banking institutions in Indonesia and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that fiqh muamalah significantly reduces both fraud intention and fraudulent behavior, indicating its dual role as a jurisprudential and ethical safeguard. Religiosity is found to negatively affect fraud intention but does not directly influence fraudulent behavior, suggesting that its ethical impact operates primarily through cognitive and intentional processes. Furthermore, fraud intention emerges as a strong predictor of fraudulent behavior, confirming its central role in translating ethical vulnerability into misconduct. These results highlight the importance of integrating Sharia-based legal knowledge with moral internalization in fraud prevention strategies. The study contributes to Islamic economics by providing empirical evidence that ethical resilience in Islamic banking depends not only on institutional compliance but also on individual moral intention and jurisprudential understanding.